Adam and Eve - Penny Frank; Tony Morris (UK USA Lion Publishing, 1985)
Retells the Biblical story of Adam and Eve, who lived happily in a beautiful garden until they disobeyed God.
Australia
"A Lion book"--Cover p. [4]
Keywords: Theology: Miscellaneous (3GddGghJ(B: (3eJaQbGJs; Bible stories -- Old Testament; Theology